(untitled) (Epidemiology, Biostatistics, and Public Health, 2022)
The sufficient-component cause model is one of the most discussed recent theories in disease causation. Despite some limitations, it seems one of the best theories to explain real world phenomena. It seems that this model has many implications on the current classical research methods related to disease causation. However, these implications have not been sufficiently explored. Therefore, based on the sufficient-component cause model, this paper aims to review, identify and rectify pitfalls in the classical causation research practices, especially those related to cohort study design.